Testing Room and Window Design Parameters for Daylight Performance According To Breeam Assessment Criteria: Cases of London and Izmir - Sönmez, İrem; Kazanasmaz, Zehra Tuğçe (Izmir Institute of Technology, 2019)
Daylight affects occupants' visual performance in the indoor environment. The amount of daylight determines the quality of the interior. If daylighting is controlled properly, it provides comfortable and healthy spaces for the occupants. It is the primary light source of interior and it saves energy decreasing the use of artificial lighting in the interior. Because of these reasons, daylight performance has a significant role in environmental assessment tools. As BREEAM is the first environmental assessment tool in the world which is published in the UK, it has been the subject matter in this thesis. BREEAM has 'Daylight' section in 'Health and Wellbeing' category. The illuminance value determines whether to get the credits or not in this category. It has been known that there are architectural parameters such as window size and surface reflectance that affect the illuminance value of the interiors. Each color combination of floor, wall, and ceiling results in a significant average reflectance value. Thus, the purpose of this thesis is to test the whole impact of these room and window design parameters on daylight performance according to BREEAM(universities, colleges, and higher education-occupied spaces) criteria with the cases of London and İzmir. The daylight performance simulation models of the reference rooms generated with four material alternatives were built in RELUX, under clear and overcast sky conditions. Simulations run for London and İzmir covering solstice and equinox days. Findings were discussed in the view of daylighting criteria of BREEAM. In general, daylight criteria of BREEAM which is based on conditions of London (UK) were found to be suitable and applicable for cases in İzmir.

Doğal aydınlatma, kullanıcıların iç mekandaki görsel performansını etkiler. Doğal aydınlatma miktarı iç mekanın kalitesini belirler. Eğer doğal aydınlatma uygun şekillerde kontrol altında tutulursa kullanıcılar için konforlu ve sağlıklı mekanlar sağlar. Doğal aydınlatma iç mekanın birincil ışık kaynağıdır ve iç mekanlarda yapay aydınlatma kullanımını azaltarak enerji tasarrufu sağlar. Bu nedenlerden dolayı, doğal aydınlatma performansının çevresel değerlendirme araçlarında önemli bir rolü vardır. BREEAM dünyada yayınlanan ilk çevresel değerlendirme aracıdır ve İngiltere'de yayınlanmıştır, bu sebeple bu tezin konusu olmuştur. BREEAM'in 'Sağlık ve Refah' kategorisinde 'Doğal Aydınlatma' bölümü bulunmaktadır. Aydınlık değeri bu kategoriden kredi alınıp alınamayacağını belirler. İç mekanın aydınlık değerini etkileyen pencere boyutu ve yüzey yansıması gibi mimari parametreler olduğu bilinmektedir. Zemin, duvar ve tavanın her renk kombinasyonu önemli bir ortalama yansıtma değeri oluşturur. Bu nedenle, bu tezin amacı, oda ve pencere tasarım parametrelerinin BREEAM (üniversiteler, kolejler ve yüksek öğretimde kullanılan alanlar) kriterlerine göre Londra ve İzmir örneklerinde doğal aydınlatma performansı üzerindeki etkisini test etmektir. Dört malzeme alternatifi ile oluşturulan referans odaların günışığı performansı simülasyon modelleri RELUX programında açık ve bulutlu gökyüzü koşullarında üretildi. Simülasyonlar gündönümü ve ekinoks günlerini kapsayan şekilde Londra ve İzmir için yapıldı. Elde edilen sonuçlar BREEAM'in doğal aydınlatma kriterleri doğrultusunda tartışıldı. Genel olarak, Londra'daki (İngiltere) koşullara dayanan BREEAM'in doğal aydınlatma kriterlerinin İzmir'deki durumlar için uygun ve uygulanabilir olduğu tespit edildi.
Oda ve Pencere Tasarım Parametrelerinin Breeam Değerlendirme Kriterlerine Göre Doğal Aydınlatma Performansı için Test Edilmesi: Londra ve İzmir Örneği
Thesis (Master)--Izmir Institute of Technology, Architecture, Izmir, 2019
Includes bibliographical references (leaves: 58-63)
Text in English; Abstract: Turkish and English
Keywords: BREEAM; Daylight illuminance; Window design; Izmir; London